Pengaruh Latihan Reaction Ball Dan Drill Recive Terhadap Ketepatan Passing Bawah Bola Voli Putri Upgris 2025: Studi Eksperimen pada Atlet UKM Bola Voli Putri UPGRIS - Rudi Cahyono; Yulia Ratimiasih; Bertika Kusuma Prastiwi (Universitas Hamzanwadi, 2026)
This study aims to determine the effect of reaction ball training and receive drills on the underhand passing accuracy of the UPGRIS 2025 women's volleyball team and to identify which training method is more effective for improving underhand passing skills. The issue addressed in this study is the athletes' low underhand passing accuracy, evidenced by a high percentage of failed passes during initial observations. A quantitative approach was employed using a quasi-experimental method with a two-group pretest-posttest design. The study population consisted of 32 athletes from the UPGRIS 2025 women's volleyball team, selected via purposive sampling. Data collection utilized the AAHPER underhand passing accuracy test, consisting of 20 passing attempts. Data analysis was conducted using IBM SPSS Statistics, involving the Shapiro-Wilk normality test, homogeneity test, paired sample t-test, and independent sample t-test at a significance level of 0.05. The study was carried out over 14 sessions, implementing reaction ball training and receive drills with progressively adjusted training intensity. The results indicate an improvement in the athletes' underhand passing skills following the training interventions. Reaction ball training enhanced the athletes' reaction speed and coordination, while receive drills improved the accuracy and consistency of their underhand passing technique. The study concludes that both reaction ball training and receive drills have a significant effect on the underhand passing accuracy of the UPGRIS 2025 women's volleyball team.